TANTANGAN DAKWAH DI DAERAH PERKEBUNAN KARET DAN KELAPA SAWIT TRANSMIGRAN SUMBER MAKMUR PALEMBANG - Sholehah, Mar’atus (Islamic Communication Journal, 2018)
The study of the challenges of dawah in the Sumber Makmur Palembang rubber and oil palm plantation area has not been done much by the researchers. The focus of the problem to be explored is the response and the pioneering paradigm of the pioneers of the Sumber Makmur religion towards cultural and religious diversity, as well as how the dawah strategies they developed in maintaining inter-faith harmony. Data from the research shows that the views and attitudes of the pioneers of religion in Sumber Makmur towards cultural diversity and religion, generally refer to the paradigm of respect and respect for each other. To find an effective dawah strategy and solve socio-religious problems of the transmigration community in Sumber Makmur village. In order to realize an effective Islamic dawah strategy so that it can change the condition of the community, it must be encapsulated in the components of dai, such as daI, dawah material, methods of dawah, media and the presentation of dawah in accordance with the conditions of the transmigration community. Therefore the strategy of Islamic dawah in transmigration areas must not be carried out by one institution, but must involve various parties. Obviously the government, dawah bodies, Islamic organizations, rich people and the daI themselves, should cooperate and work together in smoothing out the activities of dawah. Dawah in Sumber Makmur village focuses on improving the economy, education, health, transportation facilities, and other facilities.